Romania : Ex-Post Evaluation of Exceptional Access Under the 2013 Stand-By Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Romania. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses Romania's Ex-Post Evaluation of Exceptional Access under the 2013 Stand-by Arrangement. Romania experienced strong economic growth in 2016, resulting in a closed output gap. Private consumption was boosted by an expansionary and procyclical fiscal policy and wage increases. The cyclically adjusted budget deficit grew by 1.5 percent of GDP in 2016, reflecting large tax rate cuts and wage increases. Growth is expected to reach 4.2 percent in 2017-supported by continued stimulus to private consumption from a new round of fiscal relaxation and wage increases-and to moderate to 3.5 percent in the medium term.